A systematic literature review on factors influencing the adaptation behaviour of climate variability in agriculture - Sakeel Ganesh, M; Sriram, N; Balasubramaniam, P; Vijayabhama, M; Mohammed Ghouse, L; Dheebakaran, G A (Plant Science Today, 2025)
Climate variability adaptation encompasses measures implemented to adjust to the impacts of climate variability, aiming to minimize associated risks and vulnerabilities. It entails creating plans to shield economies, ecosystems and people from the negative effects of climate variability. Reducing the negative effects of climatic variability, safeguarding livelihoods and promoting sustainable development are crucial. It enhances resilience, reduces vulnerabilities and protects infrastructure, ecosystems and human welfare. Analyzing factors affecting adaptation behaviour aids in identifying challenges and potential opportunities for successful response strategies. This paper analyzes climate variability in agriculture, explored the factors influencing adaptation behaviour. A systematic literature review was conducted in published papers (i.e., over the last ten years) from the Scopus database using PRISMA methodology. This review identified 40 articles that answered three important questions: What trends are emerging in the global literature to explain climate variability adaptation? What factors are considered when shaping climate variability adaptation? Which elements can be regarded as critical to advancing adaptation mainstreaming in policy and practice? Thematic analysis showed that decision making, farmers’ perspective, environmental policy and agricultural extension were the most important elements influencing climate variability adaptation. Food security plays a modest role in climate variability adaptation. Strong governance, policy integration, stakeholder involvement and proper financing have all been identified as critical components for furthering climate variability adaptation mainstreaming.